Divalent Metal- and High Mobility Group N Protein-Dependent Nucleosome Stability and Conformation - Ong, Michelle S.; Vasudevan, Dileep; Davey, Curt A. (Journal of Nucleic Acids, 2010)
High mobility group N proteins (HMGNs) bind specifically to the nucleosome core and act as chromatin unfolding and activating factors. Using an all-Xenopus system, we found that HMGN1 and HMGN2 binding to nucleosomes results in distinct ion-dependent conformation and stability. HMGN2 association with nucleosome core particle or nucleosomal array in the presence of divalent metal triggers a reversible transition to a species with much reduced electrophoretic mobility, consistent with a less compact state of the nucleosome. Residues outside of the nucleosome binding domain are required for the activity, which is also displayed by an HMGN1 truncation product lacking part of the regulatory domain. In addition, thermal denaturation assays show that the presence of 1 mM Mg2+> or Ca2+ gives a reduction in nucleosome core terminus stability, which is further substantially diminished by the binding of HMGN2 or truncated HMGN1. Our findings emphasize the importance of divalent metals in nucleosome dynamics and suggest that the differential biological activities of HMGNs in chromatin activation may involve different conformational alterations and modulation of nucleosome core stability.